2022
DOI: 10.1177/13506501221077777
|View full text |Cite
|
Sign up to set email alerts
|

A solution for mixed elastohydrodynamic lubrication modeling considering effects of solid particles and surface roughness

Abstract: To investigate the effects of solid particles on the point contact mixed lubrication, this paper aims to introduce solid particles into rough interfaces under mixed hydrodynamic lubrication. Statistical three-body micro-contact is utilized in modeling mixed EHL. The model is verified by comparing results without considering particles and roughness with those from classical EHL formula. Factors, such as particle physical parameters, surface roughness and operating condition acting on the system are discussed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…7 To understand and predict the transient tribological dynamics behavior of a tribo-pair, a theoretical model is required. [8][9][10][11][12][13] As a result, numerical models for simulating the dynamic behavior of journal bearing start-up processes have gained popularity in recent years. [14][15][16][17] In recent years, the numerical prediction of bearings during start-up has become increasingly sophisticated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 To understand and predict the transient tribological dynamics behavior of a tribo-pair, a theoretical model is required. [8][9][10][11][12][13] As a result, numerical models for simulating the dynamic behavior of journal bearing start-up processes have gained popularity in recent years. [14][15][16][17] In recent years, the numerical prediction of bearings during start-up has become increasingly sophisticated.…”
Section: Introductionmentioning
confidence: 99%
“…7 To understand and predict the transient tribological dynamics behavior of a tribo-pair, a theoretical model is required. 813 As a result, numerical models for simulating the dynamic behavior of journal bearing start-up processes have gained popularity in recent years. 1417…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many researchers have made valuable contributions in this field. [6][7][8][9][10] The bearing liner deformation effect was the main topic of numerous studies where scholars investigated the influences of additional factors such as thermal effect, 11,12 cavitation, 13 shaft misalignment, 14 porosity, 15 surface roughness, 16,17 turbulent effect, 18 dynamic loading, 19 and others. The drawn conclusions were that the liner elasticity reduces the pressure and the load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have established dynamic models to further investigate the mechanism of bearing damage caused by impact load (Yan et al , 2020; TU et al , 2021; Wang et al , 2022). The motion and force of the bearing element under impact load are determined by solving the differential equations (Daniel et al , 2017; Balyakin et al , 2020; Chasalevris et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The result of accelerated life experiments under high dynamic loads showed that the dynamic excitations in the experiments reduced bearing life by 80% (Gegner and Nierlich, 2008). Some scholars have established dynamic models to further investigate the mechanism of bearing damage caused by impact load (Yan et al, 2020;TU et al, 2021;Wang et al, 2022). The motion and force of the bearing element under impact load are determined by solving the differential equations (Daniel et al, 2017;Balyakin et al, 2020;Chasalevris et al, 2013).…”
Section: Introductionmentioning
confidence: 99%